MELANOPHORA RORALIS (LINNAEUS, 1758) (DIPTERA: RHINOPHORIDAE) PRIMER REGISTRO DE LA FAMILIA EN URUGUAY - Martínez, María; Nihei, Silvio Shigueo (Boletín de la Sociedad Zoológica del Uruguay, 2018)
Melanophora roralis (Linnaeus, 1758) (Diptera: Rhinophoridae) family first registry in Uruguay. Rhinophoridae (Diptera: Oestroidea) is a small family of calyptrate dipterans with around 150 species and 24 genera in the world. Seven genera and 24 species are distributed in the American continent. The palearctic species Melanophora roralis (Linnaeus, 1758) in Uruguay is recorded for the first time, based on adult specimens captured in Montevideo in 2018. Its larvae are endoparasitic in terrestrial isopods (Crustacea).